Why We Should See YouTube From Digital Ecology Perspective - Romdhi Fatkhur Rozi; Rachmah Ida; Budi Irawanto; Romdhi Fatkhur Rozi (Jurnal Ilmu Komunikasi, 2024)
This study is a critical perspective in exploring changes in social, cultural and political forms related to the development of contemporary communication technology. The main theme of this research is YouTube's digital space with the topic of utilizing the main features of geo-tagging, hashtags and live streaming. Researchers observed three content creators in utilizing the features of the digital platform to carry out social interactions and actions. The purpose of this study is to explain that the character of the users and the current use of digital platforms is a representation of the interaction and socio-cultural situation of contemporary society as a part of the digital ecosystem. This research is qualitative in nature with specific observations on micro phenomena, so the results are not generalizations, but in the form of data findings to support the hypothesis, namely the importance of a critical perspective of digital ecology to explain contemporary digital ecosystem phenomena. This article is supported by comparative descriptions and descriptions of the development of several theoretical models as well as social-technological changes that have occurred before. This research contributes to providing an important perspective that media and technology studies must move from discussions about human and technology interactions, to discussions about human interactions in technology. As a study of ongoing phenomena, the researcher places this research by opening up to the potential for the latest changes that can occur along with technological developments.